2000
DOI: 10.1046/j.1365-2494.2000.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of nitrogen fertilizer applications and extended grazing for the N economy of grassland

Abstract: The response of swards which have been previously grazed to N fertilizer applied in early February was studied in two experiments in Northern Ireland. The effect of N fertilizer applied at a range of dates in autumn and spring on swards for out‐of‐season utilization was studied in a further experiment. Deep soil coring was also undertaken, subsequent to grazing with dairy cows, in grazed and protected areas in November and March to investigate the effect of out‐of‐season grazing on soil mineral N levels. Dry‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…However, both of those experiments had higher average herbage masses during the winter period (approximately 1950 kg DM ha −1 ) compared with this experiment (approximately 1700 kg DM ha −1 ), which would result in accelerated sward senescence (Carton et al. , 1988a,b; Laidlaw et al. , 2000).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…However, both of those experiments had higher average herbage masses during the winter period (approximately 1950 kg DM ha −1 ) compared with this experiment (approximately 1700 kg DM ha −1 ), which would result in accelerated sward senescence (Carton et al. , 1988a,b; Laidlaw et al. , 2000).…”
Section: Discussionmentioning
confidence: 63%
“…High LAI results in increased herbage mass which eventually restricts the quantity of light reaching the lower leaves of tillers and the tiller buds, resulting in reduced tiller production and increased senescence (Davies, 1972; Hunt, 1978). Laidlaw et al. (2000) and Hennessy et al.…”
Section: Discussionmentioning
confidence: 99%
“…(1961a), Wilkinson (1985) and Skinner and Allen (1991) for N applied specifically to produce herbage for late autumn/winter utilization. However, recent work by Laidlaw et al . (2000) has shown that, when N fertilizer is applied after late September, the response is poor and the probability for loss of N by leaching is increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, in their study, the uncut sward had a very high herbage mass entering the winter, almost 4 t DM ha –1 being removed from the cut sward in December when cut to 5 cm. This dense canopy may have resulted in a severe reduction in tiller density, adversely affecting spring growth ( Laidlaw et al ., 2000 ). Damaging effects of the grazing animal due to treading and poaching may have also contributed to the negative effects on spring herbage mass in the studies by Roche et al .…”
Section: Discussionmentioning
confidence: 99%